IMPLEMENTASI PEMBELAJARAN DENGAN KURIKULUM 2013 DI KELAS V SD NEGERI 111 PEKANBARU - Vonny Tri Mulya; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The purpose of this study was to describe the implementation of learning with curriculum 2013 in 5 th grade students at sdn 111 pekanbaru. As for the benefits of this research is to improve the quality and the quality of learning in implementing learning with curriculum 2013 in 5 th grade students at sdn 111 pekanbaru. Where the implementation of this research is class country vb sdn 111 pekanbaru whereas when the research process from april 2015 in the second semester of the 2015/2016 academic year. This form of research is descriptive qualitative research. As for who is the subject of this study is one teacher class vb sdn 111 pekanbaru. Data collection techniques in this study observation and documentation. While the technique of data analysis: data reduction, data display, conclusion and verification. Implementation of learning that teachers as a whole are in accordance with the curriculum 2013. Implementation of learning undertaken by teacher very good. Some shortcoming in implementation ; delivery of learning steps that teachers never explain to students what are the steps that will be passed during the learning proces, In evaluating the teacher does not provide evaluation questions to students, teachers also rarely collect the student’s work as a student portofolio, the follow up of teachers Failed to give follow-up is motivating students to learn the material at home, on the implementation of the scientific approach is still lagging 1st stage teachers are at the stage to question, on the implementation of authentic assessment of teachers did not do so during the learning process. Kind of attitude assessment, knowledge and skills.Key Words: curriculum 2013